The limits of U.S. hegemony in Bolivia regarding cocaine interdiction - Bostock, John Trevor (My University, 2014)
Bolivia is one of the poorest countries in Latin America, yet has nonetheless recently defied pressure from the United States to uphold its preferred approach to the ‘war on drugs’. The objective of this research project is to understand how and why Bolivia has recently altered its domestic and international policy towards cocaine interdiction over the last decade. These recent shifts in policy towards cocaine in Bolivia are important, because they speak to the larger question of whether – and to what extent - the regional hegemony of the United States in Latin America has declined in recent times. As is well known, the United States has long played a major role in shaping the policies adopted by states in Latin America in various areas, yet the recent Bolivian defection from the high profile ‘war on drugs’ suggests definite limits to recent US influence. To help assess the causes and consequences of recent policy changes within Bolivia, this thesis draws upon a number of different theoretical approaches, including international regime theory, theories of norms and language, theories of globalization and markets, and Gramscian theories of Hegemony. Drawing upon information from the United Nations Office for Drugs and Crime (hereafter UNODC) and other sources as supporting material, the thesis argues that recent developments suggest that U.S. hegemony in Latin America has significantly eroded over the last decade, at least as far as the ‘war on drugs’ is concerned. Considered alongside a number of ongoing regional trends, Bolivia can be best regarded as a successful “first mover’’ in its approach to coca interdiction, and as a consequence of its recent change in policy the US has found it difficult to maintain its preferred approach to cocaine interdiction. Since U.S. policies have become increasingly unacceptable to the rest of Latin America, the U.S. is now obliged to either work with Latin America on cocaine interdiction or be shut out.